Pyrolytic stage evolution mechanism of Zhundong coal based on reaction consistency analysis of mono/multi molecular models. (1st February 2023) - Xin, Haihui; Zhou, Banghao; Tian, Wenjiang; Qi, Xu-yao; Zheng, Mo; Lu, Wei; Yang, He; Zhong, Xiaoxing; Wang, Deming
Highlights: The Mono/Multi molecular models of LHG jet coal were constructed and verified. The pyrolysis process of LHG jet coal was simulated by the ReaxFF MD method. The pyrolysis process was divided into 3 stages including 3 key pyrolysis paths. The formation mechanisms and reaction pathways of CO, H2 S were revealed. The detail chemical reactions of LHG jet coal pyrolysis were shown. Abstract: Zhundong coalfield is the largest coalfield in China and the unclear stage evolution mechanism of Zhundong coal pyrolysis is the key factor restricting its coal fire control. Here, the monomolecular model (299 atoms) and large-scale multimolecular model (5083 atoms) were constructed for Liu huanggou (LHG) coal from Zhundong coalfield. The pyrolysis processes of the two models were calculated by ReaxFF MD method. Based on the reaction consistency analysis, the reaction paths tracing on pyrolysis stage evolution and toxic gases formation mechanisms were obtained. The LHG coal pyrolysis process is mainly because of the breakages of the ether oxygen bridge bonds, thioether bridge bonds and aliphatic hydrocarbon bridge bonds. It begins with the shedding of small molecules and then undergoes the thermal decomposition of the main structure and pyrolytic fragments. During the pyrolysis process, the LHG coal has constantly broken out tars, gases and other key products, accompanied by a large number of free radicals and intermediates produced. The main sources of CO are the active reaction sites where the carbonyl group and the carboxyl group located; H2 S is directly produced from the sulfhydryl group. The research results will guide the staged control and directional transformation of coal fire.